2017
DOI: 10.1097/md.0000000000007530
|View full text |Cite
|
Sign up to set email alerts
|

Pramipexole-induced limb dystonia and its associated complex regional pain syndrome in idiopathic Parkinson's disease

Abstract: Rationale:This case may be due to basal ganglia dysfunction, which was probably caused by abnormal activation of dopamine 1-like receptor (D1R) boosted by pramipexole binding on dopamine 3-like receptor (D3R) in a situation where D3R was overexpressed by the chronic treatment of L-dopa.Patient concerns:Striatal hand and foot deformities.Diagnoses:Striatal hand and foot deformities with CRPS.Interventions:Steroid treatemnt and withdrawal of the pramipexole.Outcomes:Recovered significantly.Lessons:Since the degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…CRPS is a chronic pain condition of modest prevalence in the overall population and relatively high incidence after injuries and surgeries to the extremities 3 21–23. Immobilization due to the fracture of an extremity is a common set of circumstances leading to CRPS 23.…”
Section: Discussionmentioning
confidence: 99%
“…CRPS is a chronic pain condition of modest prevalence in the overall population and relatively high incidence after injuries and surgeries to the extremities 3 21–23. Immobilization due to the fracture of an extremity is a common set of circumstances leading to CRPS 23.…”
Section: Discussionmentioning
confidence: 99%
“…This was probably due to two reasons: 1) an insufficient amount or duration of intrathecal IL-10 administration to prevent the transition to the chronic stage despite the effective decrease of neuro-inflammation in the acute stage of CRPS; 2) the possibility of central sensitization by mechanisms other than neuro-inflammation by spinal glial activation, such as supra-spinal structures. Considering that some clinical studies have shown evidence that other than the spinal cord, the prefrontal cortex, 34 thalamus, 8 and the basal ganglia, 35 play an important role in the development of central sensitization of CRPS, further studies will be needed to elucidate the underlying mechanism of central sensitization other than neuro-inflammation in the CRPS.…”
Section: Discussionmentioning
confidence: 99%
“…Journal of Pain Research 2020:13 contributes a little more to the acute stage of CRPS than to the chronic stage. [23][24][25][26][27][28] The disease durations were 2.4 ± 0.9 and 1.6 ± 0.7 years in studies conducted in 2017 and 2010, respectively. 15,16 Therefore, the greater effect of IVIG in the study by Goebel et al in 2010 16 compared to 2017 15 may be explained by the enrollment of patients in a relatively early phase of CRPS.…”
Section: Dovepressmentioning
confidence: 96%